2010
DOI: 10.1007/s11104-010-0366-6
|View full text |Cite
|
Sign up to set email alerts
|

Grassland responses to grazing: effects of grazing intensity and management system in an Inner Mongolian steppe ecosystem

Abstract: The major aims of this study were, firstly, to analyse the grazing-induced steppe degradation process and, secondly, to identify an efficient and sustainable grazing management system for the widely degraded Inner Mongolian typical steppe ecosystem. From 2005-2008 a grazing experiment was conducted to compare two grazing management systems, the Mixed System (MS) and the Traditional System (TS), along a gradient of seven grazing intensities, i.e. ungrazed (GI0), verylight (GI1), light (GI2), light-moderate (GI3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
224
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 303 publications
(250 citation statements)
references
References 44 publications
15
224
0
4
Order By: Relevance
“…Among these, overgrazing is regarded as a dominant factor in causing grassland degradation [4]. Previous studies have shown that degraded grassland induced by overgrazing is characterized by reductions in vegetation coverage, biodiversity, and biomass [5,6]. Moreover, heavy grazing has resulted in soil vulnerability to water and nutrient loss while also decreasing the plant available water [7].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, overgrazing is regarded as a dominant factor in causing grassland degradation [4]. Previous studies have shown that degraded grassland induced by overgrazing is characterized by reductions in vegetation coverage, biodiversity, and biomass [5,6]. Moreover, heavy grazing has resulted in soil vulnerability to water and nutrient loss while also decreasing the plant available water [7].…”
Section: Introductionmentioning
confidence: 99%
“…The potential reason was that the continuous removal of standing biomass by livestock and the corresponding decrease in above-and belowground biomass (Schönbach et al 2011). Meanwhile, the UG and LG had more grasses and less forbs (P < 0.01) compared to MG and HG (Table 2), maybe the reason of the dominated species (grasses species of Stipa bungeana and S. grandis, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…Although the cost of haymaking (128 yuan ha -1 ) is less than the value of the hay made (340 yuan ha -1 ), it is obviously more justified to leave the grassland for grazing and so save the unnecessary cost of the mowing operation. Wan et al (2011) and Schönbach et al (2011) tested a mixed land-management system in the study region in which grasslands were alternatively grazed and mowed from year to year, and suggested it was a better system than the traditional continuous grazing system. Our results support the mixed grasslandmanagement system but suggest that a more adaptive mowing strategy should be used as the basis of forage production, that is, to mow the grassland in highproduction years and graze in low-production years.…”
Section: Management Implicationsmentioning
confidence: 99%